The Effect of Tomato Paste Addition on the Quality of Catfish Nuggets and Estimation of Shelf Life by ASLT (Accelerated Shelf-Life Testing) Method Based on Arrhenius Approach. - Ernando Setyo Dharmanto; Ulya Sarofa; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Catfish nuggets are a type of processed restructured fish meat, namely catfish meat (Clarias sp) which is ground and seasoned, steamed then covered with flour adhesive, breadcrumb coating (breading), and fried. In this research, the manufacture of catfish nuggets with the addition of tomato paste was studied. Tomato paste is used to improve color, texture, fiber addition, and the addition of antioxidant compounds in catfish nuggets. The purpose of this study was to determine the effect of the addition of tomato paste on the quality and organoleptic properties of catfish nuggets, and to estimate the shelf life of catfish nuggets products with the addition of tomato paste in the best treatment. This study used a single-factor Completely Randomized Design (CRD) with three replications. Where the factor is the concentration of tomato paste added consisting of six levels (0%, 10%, 15%, 20%, 25%, 30% w/b). Data were analyzed using ANOVA and BNT further test at 5% level and organoleptic test using scoring test with 25 trained panelists. The treatment of adding 30% concentration of tomato paste is the best treatment that produces tomato paste catfish nuggets with moisture content of 59.974% ± 0.495, ash content of 1.991% ± 0.120, protein content of 7.840% ± 0.092, fat content of 1.583% ± 0.271, carbohydrate content 28.612% ± 0.742, crude fiber content 0.413% ± 0.025, vitamin C content 4.713 mg/100g ± 0.042, and organoleptic test color 4.36 (slightly yellow), texture 4.44 (slightly chewy), aroma 3.84 (slightly pleasant) and taste 3.92 (slightly savory). The best catfish nuggets with 30% paste addition had a shelf life of 12 days at 25°C, a shelf life of 94 days at 3°C, and a shelf life of 474 days at -12°C.